Aluminum alloy material for heat exchanger fins and manufacturing method of aluminum alloy material

By adjusting the chemical composition and manufacturing process of the aluminum alloy, an aluminum alloy material with excellent mechanical properties and corrosion resistance was prepared, which solved the problem of low performance of the existing Al-Mn-type heat transfer materials, and achieved high post-weld strength and corrosion resistance.

CN119663080APending Publication Date: 2025-03-21SHANDONG INNOVATION ADDITIVE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844564.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The Al-Mn-type heat transfer materials represented by the existing 3003 aluminum alloy have low comprehensive performance in the automotive industry and are difficult to meet the high performance requirements.

Method used

By adjusting the chemical composition of the aluminum alloy, increasing the content of Si, Mn, Zn, Mg, Cu, Sr and Mo, and using specific manufacturing process steps, such as smelting, casting, hot rolling, cold rolling and annealing, aluminum alloy materials with excellent mechanical properties and corrosion resistance are prepared.

Benefits of technology

The high post-weld strength and excellent corrosion resistance of aluminum alloy materials are achieved. The tensile strength after welding is greater than 140MPa, the corrosion potential is significantly improved, and the sag resistance value is less than 4mm, which significantly improves the product's service performance and life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188849830000151
    Figure BDA0005188849830000151
Patent Text Reader

Abstract

The invention discloses an aluminum alloy material for heat exchanger fins and a manufacturing method of the aluminum alloy material, and relates to the technical field of aluminum alloys for heat exchanger fins, and the aluminum alloy material comprises the following elemental components by weight percent: 0.15-0.45% of Si; 0.85 to 1.45% by weight of Mn; zn: 1.24 to 1.58 wt%; 0.10 to 0.30 wt% of Mg; cu: 0.05 to 0.20 wt%; sr: 0.05 to 0.20 wt%; mo: 0.03 to 0.15 wt%; not more than 0.05% of impurity elements and the balance of Al. The alloy is manufactured through the steps of smelting, refining, degassing, deslagging, casting, homogenizing, hot rolling, cold rolling, annealing, final rolling and the like. After high-temperature brazing, the aluminum alloy material has high post-welding strength, excellent corrosion resistance and sag resistance and good use performance and service life, and the defect that an Al-Mn series heat transfer material represented by 3003Al alloy is insufficient in performance at present is overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys for heat exchanger fins, and in particular to an aluminum alloy material for heat exchanger fins and a manufacturing method thereof. Background Art

[0002] Aluminum alloy is the most widely used type of non-ferrous metal structural material in industry. It has been widely used in aviation, aerospace, automobile, machinery manufacturing, shipbuilding and chemical industries. With the rapid development of science and technology and industrial economy in recent years, the demand for aluminum alloy structural parts has increased, and the research on aluminum alloy has also deepened. The wide application of aluminum alloys has promoted the development of aluminum alloy technology. Among them, Al-Mn series heat transfer materials represented by 3003Al alloy are widely used in heat exchanger parts such as radiators, evaporators, and condensers. The rapid development of the automotive industry requires heat transfer materials to have better mechanical properties and more effective heat dissipation and corrosion resistance. Therefore, traditional Al-Mn series alloys will be difficult to meet the high performance requirements in the future, and new alloys must be developed through alloying design. Al-Mn series alloy strips for heat exchanger fins are generally manufactured by casting, hot rolling, cold rolling and annealing. The control of the chemical composition and process parameters of the alloy strips is the key to obtaining high-performance fins. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide an aluminum alloy material for heat exchanger fins and a method for manufacturing the same, aiming to improve various performances of the aluminum alloy material for heat exchanger fins and meet usage requirements.

[0004] In order to achieve the above object, the aluminum alloy material of the present invention comprises the following element components by weight percentage:

[0005] Si: 0.15 to 0.45 wt%;

[0006] Mn: 0.85 to 1.45 wt%;

[0007] Zn: 1.24 to 1.58 wt. %;

[0008] Mg: 0.10 to 0.30 wt. %;

[0009] Cu: 0.05 to 0.20 wt%;

[0010] Sr: 0.05 to 0.20 wt%;

[0011] Mo: 0.03 to 0.15 wt%;

[0012] Impurity elements: not more than 0.05%;

[0013] Al: margin.

[0014] Furthermore, the method for manufacturing the aluminum alloy material is carried out according to the following steps:

[0015] Step 1: select industrial pure aluminum ingots, magnesium ingots, zinc ingots, aluminum silicon master alloy ingots, aluminum manganese master alloy ingots, aluminum copper master alloy ingots, aluminum strontium master alloy ingots and aluminum molybdenum master alloy ingots in turn, calculate the components according to the above Table 1 and prepare the materials, add them into a smelting furnace and melt them at a temperature of 720°C-740°C, keep them warm for 1 hour and stir them thoroughly, then put them into a static furnace, the refining temperature in the static furnace is 740°C-760°C, and refine, degas and remove slag;

[0016] Step 2: Casting is performed on a semi-continuous casting machine to obtain a casting alloy billet with a thickness of 30 to 60 mm, and the casting alloy billet is milled on a milling machine to remove various casting defects on the surface of the ingot, and no aluminum sheets or aluminum chips are allowed to adhere, and there is no burr on the edge;

[0017] Step 3: homogenize the ingot at a temperature of 540°C-560°C for 2.5 hours, and then cool to room temperature;

[0018] Step 4: The ingot is then preheated in a heating furnace at 485-515°C, and then hot-rolled for at least 21 passes to obtain an alloy strip with a thickness of 4.5 mm, and the final rolling temperature is 315°C-335°C;

[0019] Step 5: The alloy strip is subjected to heat treatment annealing at a temperature of 355°C-375°C for 5 hours, and then cold rolled on a cold rolling mill, and rolled into 0.15 mm aluminum foil through 6 passes;

[0020] Step 6: Place the 0.15 mm thick aluminum foil in an annealing furnace for intermediate annealing at a temperature of 425°C-445°C for 3 hours, and then cool to room temperature with the furnace;

[0021] Step 7: The 0.15 mm aluminum foil after intermediate annealing is rolled into 0.06-0.08 mm aluminum foil in one pass on a cold rolling mill.

[0022] Furthermore, the casting temperature is 705° C., the casting speed is 42 mm / min, and the cooling water flow rate is 220 m / h.

[0023] Furthermore, the heating rate to reach the above homogenization temperature is 80°C / hour, and the cooling rate is 120°C / hour.

[0024] Furthermore, the cold rolling passes are: 4.5mm, 2.6mm, 1.2mm, 0.68mm, 0.37mm, 0.23mm, 0.15mm.

[0025] Furthermore, the heating rate to reach the intermediate annealing temperature is 60° C. / hour.

[0026] Compared with the prior art, the present invention has the following beneficial effects: the characteristics of the aluminum alloy material for the heat exchanger wing in the embodiment of the present application are obtained by changing the alloy composition ratio (compared with 3003 aluminum alloy, especially adding strontium and molybdenum, and changing the content of other main elements) and / or the manufacturing process. This aluminum alloy material has high post-weld strength and excellent corrosion resistance after high-temperature brazing. Specifically, the aluminum alloy material for the wing in the embodiment of the present application has a post-weld tensile strength greater than 140MPa, and a corrosion potential of about -700mV (significantly higher than 3003 aluminum alloy). In addition, the anti-sagging value is even lower than 4mm, thereby better ensuring that the tube-fin structure has excellent anti-sagging performance during brazing, will not collapse and melt, and significantly improves the performance and life of the product. DETAILED DESCRIPTION

[0027] The specific implementation modes of the present invention are further described below in conjunction with examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0028] The embodiments of the present application provide an aluminum alloy material for heat exchanger fins and a method for manufacturing the same, thereby solving the problem of low comprehensive performance of Al-Mn series heat transfer materials represented by 3003 aluminum alloy in the prior art.

[0029] (i) The technical solution in the embodiment of the present application is to solve the above technical problems. The aluminum alloy material for heat exchanger fins developed comprises the elemental composition shown in Table 1 below:

[0030] Table 1: Chemical composition of aluminum alloy materials for heat exchanger fins

[0031] Serial number element Content (weight percentage) 1 Silicon (Si) 0.15 to 0.45 wt% 2 Manganese (Mn) 0.85 to 1.45 wt% 3 Zinc (Zn) 1.24 to 1.58 wt% 4 Magnesium (Mg) 0.10 to 0.30 wt% 5 Copper (Cu) 0.05 to 0.20 wt% 6 Strontium (Sr) 0.05 to 0.20 wt% 7 Molybdenum (Mo) 0.03 to 0.15 wt% 8 Impurity Elements Not more than 0.05% by weight 9 Aluminum (Al) margin

[0032] The silicon content in the present application can promote the formation of dispersoids, improve the mechanical strength of the aluminum alloy before and after brazing, and thus produce an alloy with excellent mechanical properties and corrosion potential. Specifically, Si in combination with Mg and Mn can produce high-density dispersoid particles, thereby promoting high strength and good anti-sagging properties. The silicon content is 0.15 to 0.45% by weight. If the silicon content is lower than 0.15% by weight, the performance of the aluminum alloy will not meet expectations; if the silicon content is higher than 0.45% by weight, the high content of excess silicon in this system will become an impurity element, which will not only affect the performance of the alloy but also may increase the risk of melting corrosion of the fin blank during brazing; in some instances %, about 0.20 to about 0.40 wt. %, about 0.25 to about 0.35 wt. %, about 0.15 to about 0.40 wt. %, about 0.15 to about 0.35 wt. %, about 0.15 to about 0.30 wt. %, about 0.15 to about 0.25 wt. %, about 0.20 to about 0.45 wt. %, about 0.25 to about 0.45 wt. %, about 0.30 to about 0.45 wt. %, about 0.35 to about 0.45 wt. %. Still further, the silicon content can be about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34%, about 0.35%, about 0.36%, about 0.37%, about 0.38%, about 0.39%, about 0.40%, about 0.41%, about 0.42%, about 0.43%, about 0.44% or about 0.45%.

[0033] The manganese content of the present application can be dissolved into the Al alloy matrix, play a role in strengthening the aluminum alloy matrix, and can also inhibit the grain growth of primary Si and α-Al, so that the primary Si content is dispersed and distributed between the grains, playing a role of dispersion strengthening, thereby improving the strength, toughness and anti-sagging properties of the aluminum alloy material. The manganese content is 0.85 to 1.45% by weight. If the manganese content is lower than 0.85% by weight, the performance of the aluminum alloy will not meet expectations; if the manganese content is higher than 1.45% by weight, it may affect the thermal conductivity and plasticity of the aluminum alloy material, affect the use effect of the fin, and there is a risk of easy fracture of the aluminum alloy material. In some examples, the manganese content can further be about 0.90 to about 1.40 weight %, about 0.95 to about 1.35 weight %, about 1.0 to about 1.30 weight %, about 1.05 to about 1.25 weight %, about 1.10 to about 1.20 weight %, about 0.85 to about 1.35 weight %, about 0.85 to about 1.25 weight %, about 0.85 to about 1.15 weight %, about 0.85 to about 1.05 weight %, about 0.85 to about 0.95 weight %, about 0.95 to about 1.45 weight %, about 1.05 to about 1.45 weight %, about 1.15 to about 1.45 weight %, about 1.25 to about 1.45 weight %, about 1.35 to about 1.45 weight %. Furthermore, the silicon content can be about 0.85%, about 0.86%, about 0.87%, about 0.88%, about 0.89%, about 0.90%, about 0.91%, about 0.92%, about 0.93%, about 0.94%, about 0.95%, about 0.96%, about 0.97%, about 0.98%, about 0.99%, about 1.00%, about 1.01%, about 1.02%, about 1.03%, about 1.04%, about 1.05%, about 1.06%, about 1.07%, about 1.08%, about 1.09%, about 1.10%, about 1.11%, about 1.12%, about 1.13%, about 1.14%, about 1.15%, about 1.16%, about 1.17%, about 1.18%, about 1.19%, about 1.20%, about 1.21%, about 1.22%, about 1.23%, about 1.24%, about 1.25%, about 1.26%, about 1.27%, about 1.28%, about 1.29%, about 1.30%, about 1.31%, about 1.32%, about 1.33%, about 1.34%, about 1.35%, about 1.36%, about 1.37%, about 1.38%, about 1.39%, about 1.40%, about 1.41%, about 1.42%, about 1.43%, about 1.44%, about 1.45%, about 1 about 1.40%, about 1.41%, about 1.42%, about 1.43%, about 1.44%, or about 1.45%.

[0034] The zinc content of the present application can play a sacrificial role on the aluminum alloy. The zinc content in the present system is 1.24 to 1.58% by weight. The aluminum alloy with this zinc content is used for fins, and the corrosion potential difference of the fins can be adjusted to obtain a sufficient level of protection, and the Zn content can improve the corrosion resistance of the aluminum alloy. If the zinc content is lower than 1.24% by weight, the performance of the material will not meet expectations; if the zinc content exceeds 1.58% by weight, the corrosion resistance of the alloy will be reduced, and the fins may be perforated during use, thereby damaging the mechanical integrity and thermal performance of the heat exchanger, thereby affecting the service life of the heat exchanger. In some examples, the zinc content can further be about 1.26 to about 1.56 weight %, about 1.28 to about 1.54 weight %, about 1.30 to about 1.52 weight %, about 1.32 to about 1.50 weight %, about 1.34 to about 1.48 weight %, about 1.36 to about 1.46 weight %, about 1.38 to about 1.44 weight %, about 1.40 to about 1.42 weight %. Still further, the zinc content can be about 1.24%, about 1.25%, about 1.26%, about 1.27%, about 1.28%, about 1.29%, about 1.30%, about 1.31%, about 1.32%, about 1.33%, about 1.34%, about 1.35%, about 1.36%, about 1.37%, about 1.38%, about 1.39%, about 1.40%, about 1.41%, about 1.42%, about 1.43%, about 1.44%, about 1.45%, about 1.46%, about 1.47%, about 1.48%, about 1.49%, about 1.50%, about 1.51%, about 1.52%, about 1.53%, about 1.54%, about 1.55% or about 1.56%.

[0035] The magnesium content in this application can form a stable Mg2Si compound with silicon, which can greatly improve the mechanical properties of aluminum alloy materials, and improve the toughness by cooperating with Sr modification treatment to improve the morphology of the strengthening phase. In addition to strengthening, magnesium can also improve the corrosion resistance of aluminum alloys. The content of magnesium in this system is 0.10 to 0.30% by weight. If the content of magnesium is lower than 0.10% by weight, the performance of the material will not meet expectations; if the content of magnesium exceeds 0.30% by weight, the solubility of magnesium in the aluminum alloy of this system is limited, and the precipitation rate is not ideal. Excessive magnesium will form excess phases between grains, which will reduce the strength at the grain boundaries and cause the aluminum alloy material to become brittle. In some examples, the magnesium content can further be about 0.15 to about 0.25 weight %, about 0.15 to about 0.20 weight %, about 0.20 to about 0.25 weight %, about 0.10 to about 0.25 weight %, about 0.10 to about 0.20 weight %, about 0.10 to about 0.15 weight %, about 0.15 to about 0.30 weight %, about 0.20 to about 0.30 weight %, about 0.25 to about 0.30 weight %. Still further, the magnesium content can be about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29% or about 0.30%.

[0036] The copper content of the present application can form a solid solution phase with aluminum, and dispersedly distributed on the grain boundary of the aluminum alloy through the precipitated Al2Cu phase. The precipitated phase is a strengthening phase, which can improve the strength and toughness of the aluminum alloy after brazing, and can help to form large pancake grains, thereby improving the anti-sagging characteristics. The copper content is 0.05 to 0.20% by weight. If the copper content is lower than 0.05% by weight, the performance of the aluminum alloy will not meet expectations; if the copper content is higher than 0.20% by weight, it may cause the corrosion performance of the alloy material to decrease, and the positive corrosion potential caused by it is undesirable for aluminum alloy fins. In some examples, the copper content can be further about 0.05 to about 0.15% by weight, about 0.05 to about 0.10% by weight, about 0.10 to about 0.20% by weight, and about 0.15 to about 0.20% by weight. Still further, the copper content can be about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19% or about 0.20%.

[0037] The strontium content in the present application can have a metamorphic effect on the aluminum alloy. The addition of strontium can simultaneously refine the α dendrites and eutectic silicon in the aluminum alloy, while improving the morphology of the overall organization, thereby improving the plastic workability of the alloy and the final fin quality. The strontium content in the embodiments of the present application is 0.05 to 0.20% by weight. Excessive strontium in this system exceeding 0.2% is likely to lead to over-metamorphism and increased hydrogen absorption tendency, thereby affecting the final quality of the product. In some examples, the strontium content can further be about 0.06 to about 0.19 weight %, about 0.07 to about 0.18 weight %, about 0.08 to about 0.17 weight %, about 0.09 to about 0.16 weight %, about 0.10 to about 0.15 weight %, about 0.11 to about 0.14 weight %, about 0.12 to about 0.13 weight %, about 0.05 to about 0.10 weight %, about 0.10 to about 0.15 weight %, about 0.05 to about 0.15 weight %, about 0.10 to about 0.20 weight %, about 0.15 to about 0.20 weight %. Still further, the strontium content can be about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19% or about 0.20%.

[0038] The molybdenum content of the present application can generate Mo3Al8 strengthening phase with the matrix Al in the aluminum alloy, and under the synergistic effect of Sr and Mo, a fin aluminum alloy with high strength and good thermal conductivity can be obtained. The addition amount of molybdenum in this system is 0.03 to 0.15% by weight. The addition amount is less than 0.03%, which will lead to the aluminum alloy achieving the expected effect. If it is higher than 0.15%, it may have a greater impact on the corrosion resistance of the material. In some examples, the molybdenum content can further be about 0.04 to about 0.14 weight %, about 0.05 to about 0.13 weight %, about 0.06 to about 0.12 weight %, about 0.07 to about 0.11 weight %, about 0.08 to about 0.10 weight %, about 0.03 to about 0.12 weight %, about 0.03 to about 0.10 weight %, about 0.03 to about 0.08 weight %, about 0.03 to about 0.05 weight %, about 0.05 to about 0.15 weight %, about 0.08 to about 0.15 weight %, about 0.10 to about 0.15 weight %, about 0.12 to about 0.15 weight %. Still further, the molybdenum content may be about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, or about 0.15%.

[0039] (ii) Based on the chemical composition and content of the above-mentioned novel aluminum alloy material for heat exchanger fins, the present embodiment also proposes a method for manufacturing the aluminum alloy material for heat exchanger fins, which mainly comprises the following steps:

[0040] Step 1: select industrial pure aluminum ingots, magnesium ingots, zinc ingots, aluminum silicon master alloy ingots, aluminum manganese master alloy ingots, aluminum copper master alloy ingots, aluminum strontium master alloy ingots and aluminum molybdenum master alloy ingots, calculate the composition according to the above Table 1 and prepare the materials, add them into a smelting furnace and melt them at a temperature of 720°C-740°C, keep them warm for 1 hour and stir them thoroughly, then put them into a static furnace, the refining temperature in the static furnace is 740°C-760°C, and refine, degas and remove slag;

[0041] Step 2: Casting is performed on a semi-continuous casting machine. In order to obtain more uniform and fine casting structure grains, the casting process parameters are controlled as follows: the casting temperature is 705°C, the casting speed is 42mm / min, the cooling water flow rate is 220m / h, and the casting alloy billet with a thickness of 30-60mm is obtained; the casting alloy billet is milled on a milling machine to mill out various casting defects on the surface of the ingot, and aluminum sheets and aluminum chips are not allowed to adhere, and there is no burr on the edge;

[0042] Step 3: homogenize the ingot at a homogenization temperature of 540°C-560°C for 2.5 hours, and then cool to room temperature. The heating rate to the homogenization temperature is 80°C / hour and the cooling rate is 120°C / hour.

[0043] Step 4: The ingot is then preheated in a heating furnace at 485-515°C, and then hot-rolled for at least 21 passes to obtain an alloy strip with a thickness of 4.5 mm, and the final rolling temperature is 315°C-335°C;

[0044] Step 5: The alloy strip is subjected to heat treatment annealing at a temperature of 355°C-375°C for 5 hours, and then cold rolled on a cold rolling mill, with the cold rolling passes being: 4.5mm→2.6mm→1.2mm→0.68mm→0.37mm→0.23mm→0.15mm, and rolled to 0.15mm aluminum foil through 6 passes;

[0045] Step 6: placing the 0.15 mm thick aluminum foil in an annealing furnace for intermediate annealing at a temperature of 425°C-445°C for 3 hours, and then cooling to room temperature with the furnace, wherein the heating rate to reach the intermediate annealing temperature is 60°C / hour;

[0046] Step 7: After intermediate annealing, the 0.15 mm aluminum foil is rolled into 0.06-0.08 mm aluminum foil in one pass on a cold rolling mill, and the cold working rate is 47%-60%, thereby obtaining an aluminum alloy material for heat exchanger fins.

[0047] Example 1

[0048] This embodiment 1 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0049] Si: 0.15%;

[0050] Mn: 0.85%;

[0051] Zn: 1.24%;

[0052] Mg: 0.10%;

[0053] Cu: 0.05%;

[0054] Sr: 0.05%;

[0055] Mo: 0.03%;

[0056] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0057] Al: margin.

[0058] Example 2

[0059] This embodiment 2 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0060] Si: 0.45%;

[0061] Mn: 1.45%;

[0062] Zn: 1.58%;

[0063] Mg: 0.30%;

[0064] Cu: 0.20%;

[0065] Sr: 0.20%;

[0066] Mo: 0.15%;

[0067] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0068] Al: margin.

[0069] Example 3

[0070] This embodiment 3 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0071] Si: 0.30%;

[0072] Mn: 1.15%;

[0073] Zn: 1.41%;

[0074] Mg: 0.20%;

[0075] Cu: 0.12%;

[0076] Sr: 0.12%;

[0077] Mo: 0.10%;

[0078] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0079] Al: margin.

[0080] Example 4

[0081] This embodiment 4 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0082] Si: 0.25%;

[0083] Mn: 1.05%;

[0084] Zn: 1.35%;

[0085] Mg: 0.15%;

[0086] Cu: 0.08%;

[0087] Sr: 0.08%;

[0088] Mo: 0.06%;

[0089] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0090] Al: margin.

[0091] Example 5

[0092] This embodiment 5 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0093] Si: 0.35%;

[0094] Mn: 1.35%;

[0095] Zn: 1.50%;

[0096] Mg: 0.25%;

[0097] Cu: 0.16%;

[0098] Sr: 0.16%;

[0099] Mo: 0.12%;

[0100] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0101] Al: margin.

[0102] Comparative Example 1

[0103] This comparative example 1 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0104] Si: 0.05% ;

[0105] Mn: 1.15%;

[0106] Zn: 1.41%;

[0107] Mg: 0.20%;

[0108] Cu: 0.12%;

[0109] Sr: 0.12%;

[0110] Mo: 0.10%;

[0111] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0112] Al: margin.

[0113] Comparative Example 2

[0114] This comparative example 2 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0115] Si: 0.30%;

[0116] Mn: 0.5% ;

[0117] Zn: 1.41%;

[0118] Mg: 0.20%;

[0119] Cu: 0.12%;

[0120] Sr: 0.12%;

[0121] Mo: 0.10%;

[0122] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0123] Al: margin.

[0124] Comparative Example 3

[0125] Comparative Example 3 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in percentage by weight:

[0126] Si: 0.30%;

[0127] Mn: 1.15%;

[0128] Zn: 0.75% ;

[0129] Mg: 0.20%;

[0130] Cu: 0.12%;

[0131] Sr: 0.12%;

[0132] Mo: 0.10%;

[0133] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0134] Al: margin.

[0135] Comparative Example 4

[0136] Comparative Example 4 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in percentage by weight:

[0137] Si: 0.30%;

[0138] Mn: 1.15%;

[0139] Zn: 1.41%;

[0140] Mg: 0.50% ;

[0141] Cu: 0.12%;

[0142] Sr: 0.12%;

[0143] Mo: 0.10%;

[0144] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0145] Al: margin.

[0146] Comparative Example 5

[0147] Comparative Example 5 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0148] Si: 0.30%;

[0149] Mn: 1.15%;

[0150] Zn: 1.41%;

[0151] Mg: 0.20%;

[0152] Cu: 0.30% ;

[0153] Sr: 0.12%;

[0154] Mo: 0.10%;

[0155] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0156] Al: margin.

[0157] Comparative Example 6

[0158] Comparative Example 6 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0159] Si: 0.30%;

[0160] Mn: 1.15%;

[0161] Zn: 1.41%;

[0162] Mg: 0.20%;

[0163] Cu: 0.12%;

[0164] Sr: Not added ;

[0165] Mo: 0.10%;

[0166] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0167] Al: margin.

[0168] Comparative Example 7

[0169] Comparative Example 7 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in percentage by weight:

[0170] Si: 0.30%;

[0171] Mn: 1.15%;

[0172] Zn: 1.41%;

[0173] Mg: 0.20%;

[0174] Cu: 0.12%;

[0175] Sr:0.35% ;

[0176] Mo: 0.10%;

[0177] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0178] Al: margin.

[0179] Comparative Example 8

[0180] Comparative Example 8 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in weight percentage:

[0181] Si: 0.30%;

[0182] Mn: 1.15%;

[0183] Zn: 1.41%;

[0184] Mg: 0.20%;

[0185] Cu: 0.12%;

[0186] Sr: 0.12%;

[0187] Mo: not added ;

[0188] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0189] Al: margin.

[0190] Comparative Example 9

[0191] Comparative Example 9 discloses an aluminum alloy material for heat exchanger fins, comprising the following elemental components in percentage by weight:

[0192] Si: 0.30%;

[0193] Mn: 1.15%;

[0194] Zn: 1.41%;

[0195] Mg: 0.20%;

[0196] Cu: 0.12%;

[0197] Sr: 0.12%;

[0198] Mo: 0.30% ;

[0199] Impurity elements: not more than 0.05%, where impurity elements include but are not limited to iron (Fe), calcium (Ca), lead (Pb), etc.;

[0200] Al: margin.

[0201] Comparative Example 10

[0202] A 3003 aluminum foil alloy comprising the following elemental compositions by weight percentage:

[0203] The iron (Fe)-content range is 0.70%.

[0204] Copper (Cu)-content ranges from 0.05% to 0.20%.

[0205] Manganese (Mn)-content ranges from 1.0% to 1.5%.

[0206] The zinc (Zn) content is 0.10%.

[0207] The silicon (Si) content is 0.60%.

[0208] Test example

[0209] The aluminum foil samples of Examples 1-5 and Comparative Examples 1-10 were taken as samples to test the following items:

[0210] 1. Tensile strength: A standard tensile specimen was made according to the national standard GB / T228-2002, and the tensile strength was measured at a tensile speed of 1 mm / min on a ZwickZ20 universal tensile testing machine with a measuring length of 50 mm;

[0211] 2. The aluminum foil samples were subjected to simulated brazing heat treatment, specifically, a simulated brazing cycle was carried out at a temperature of about 605°C and then cooled to room temperature within about 20 minutes, and then the tensile strength, corrosion resistance and sag resistance of each sample were measured. The tensile strength was measured according to the national standard GB / T228-2002, and the corrosion performance test was tested according to the standard test method for corrosion potential measurement of aluminum alloys in ASTM G69-20 (the larger the corrosion potential, the better the corrosion resistance); the sag resistance was measured directly by manually using a clamping tooth.

[0212] It should be noted that the ability of aluminum alloy fin foil to resist the natural drooping due to gravity during the brazing process is called anti-droop performance (abbreviated as SAG performance). Fins and tubes are usually brazed at a high temperature of about 605°C. The fin strength is reduced and softened, deformed, or even collapsed. This may cause the tube and the heat dissipation fin to be welded loosely, or even cause cold welding or desoldering, affecting the heat dissipation effect of the heat exchanger. Therefore, anti-droop performance has become an important indicator for measuring the quality of brazed composite fin foil. The lower the anti-droop value, the better the material performance.

[0213] Table 2: Test results of each test sample

[0214]

[0215] From the data recorded in Table 2 above, it can be seen that the aluminum alloy material for heat exchanger fins prepared in the embodiment of the present application has better tensile strength and tensile strength after brazing, corrosion resistance and droop resistance than the control example, which can ensure that the aluminum alloy material has excellent and stable mechanical strength and durability when used in the heat exchanger fins, and significantly improves the performance and life of the product.

[0216] It can be seen from the comparative examples that the various properties of the aluminum alloy material for wings prepared in the embodiments of the present application are affected by the raw material ratio. By selecting the element content and / or manufacturing process within the protection scope of the present application, the aluminum alloy material prepared obviously has more excellent tensile strength, corrosion resistance and droop resistance. If the content of each element component is not within the protection scope of the present application, or some components are out of the formula, or the content of some element components does not meet the requirements, or the process steps and parameters are different from those of the present application, the above-mentioned various properties of the aluminum alloy material for wings finally obtained cannot achieve the expected effect.

[0217] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aluminum alloy material for heat exchanger fins, characterized in that: Contains the following elemental composition by weight percentage: Si: 0.15 to 0.45 wt%; Mn: 0.85 to 1.45 wt%; Zn: 1.24 to 1.58 wt. %; Mg: 0.10 to 0.30 wt. %; Cu: 0.05 to 0.20 wt.%; Sr: 0.05 to 0.20 wt%; Mo: 0.03 to 0.15 wt%; Impurity elements: not more than 0.05%; Al: margin.

2. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material has a tensile strength after welding greater than 140 MPa, a corrosion potential of about -700 mV, and an anti-sagging value of less than 4 mm.

3. The aluminum alloy material according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si: 0.15%, Mn: 0.85%, Zn: 1.24%, Mg: 0.10%, Cu: 0.05%, Sr: 0.05%, Mo: 0.03%, impurity elements: not more than 0.05%, and Al: balance.

4. The aluminum alloy material according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si: 0.45%, Mn: 1.45%, Zn: 1.58%, Mg: 0.30%, Cu: 0.20%, Sr: 0.20%, Mo: 0.15%, impurity elements: not more than 0.05%, and Al: balance.

5. The aluminum alloy material according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si: 0.30%, Mn: 1.15%, Zn: 1.41%, Mg: 0.20%, Cu: 0.12%, Sr: 0.12%, Mo: 0.10%, impurity elements: not more than 0.05%, and Al: balance.

6. A method for manufacturing an aluminum alloy material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: select industrial pure aluminum ingots, magnesium ingots, zinc ingots, aluminum silicon master alloy ingots, aluminum manganese master alloy ingots, aluminum copper master alloy ingots, aluminum strontium master alloy ingots and aluminum molybdenum master alloy ingots in turn, calculate the components according to the above Table 1 and prepare the materials, add them into a smelting furnace and melt them at a temperature of 720°C-740°C, keep them warm for 1 hour and stir them thoroughly, then put them into a static furnace, the refining temperature in the static furnace is 740°C-760°C, and refine, degas and remove slag; Step 2: Casting is performed on a semi-continuous casting machine to obtain a casting alloy billet with a thickness of 30 to 60 mm, and the casting alloy billet is milled on a milling machine to remove various casting defects on the surface of the ingot, and no aluminum sheets or aluminum chips are allowed to adhere, and there is no burr on the edge; Step 3: homogenize the ingot at a temperature of 540°C-560°C for 2.5 hours, and then cool to room temperature; Step 4: The ingot is then preheated in a heating furnace at 485-515°C, and then hot-rolled for at least 21 passes to obtain an alloy strip with a thickness of 4.5 mm, and the final rolling temperature is 315°C-335°C; Step 5: The alloy strip is subjected to heat treatment annealing at a temperature of 355°C-375°C for 5 hours, and then cold rolled on a cold rolling mill, and rolled into 0.15 mm aluminum foil through 6 passes; Step 6: Place the 0.15 mm thick aluminum foil in an annealing furnace for intermediate annealing at a temperature of 425°C-445°C for 3 hours, and then cool to room temperature with the furnace; Step 7: The 0.15 mm aluminum foil after intermediate annealing is rolled into 0.06-0.08 mm aluminum foil in one pass on a cold rolling mill.

7. The manufacturing method according to claim 6, characterized in that: The casting temperature is 705° C., the casting speed is 42 mm / min, and the cooling water flow rate is 220 m / h.

8. The manufacturing method according to claim 6, characterized in that: The heating rate to reach the above homogenization temperature was 80°C / hour and the cooling rate was 120°C / hour.

9. The manufacturing method according to claim 6, characterized in that: The cold rolling passes are: 4.5mm, 2.6mm, 1.2mm, 0.68mm, 0.37mm, 0.23mm, 0.15mm.

10. The manufacturing method according to claim 6, characterized in that: The heating rate to reach the intermediate annealing temperature was 60°C / hour.